VALIDASI SOAL-SOAL BERBASIS LITERASI MATERI PERPINDAHAN KALOR UNTUK MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Ifa Seftia Rakhma Widiyanti (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
The purpose of this study is to find a form of literacy and numeracy-based e-module with the specific aim of knowing the validity of literacy-based questions on heat transfer material for elementary school teacher education students. This research was conducted at the University of PGRI Ronggolawe Tuban (UNIROW) Primary School Teacher Education (PGSD) study program. The object of the research is PGSD UNIROW students batch 2021. The time of the research starts from February to May 2022. The research design used in this study is the Dick and Carey development model. This research design is used because it is more specific in its development. In the early stages of research, research is carried out, namely the research stage or literature study to obtain information about the needs of the product to be developed. The stages of development carried out consist of five stages, namely (1) needs analysis, (2) analysis of forms of literacy-based questions, (3) material analysis with the skills to be achieved, (4) formulating skills achievement goals, ( 5) validation of literacy-based questions. The validation results show that the expert assessment of the literacy-based questions developed is in the very good category with a percentage of 92.5%. The results of language validation get good criteria with a percentage of 75%. Based on these results, literacy-based questions deserve to be tested on students.